Odpowiedź :
Odpowiedź:
13x+7y-10x-4y+5y = - 3x+8y
5a³ +2a – a² + 3a² – 10a³ + 5 = - 5a³ + 2a² + 2a + 5
90a + 3b – a² – 81a – 2b + a² = 9a + b
4x² - x – x³ +5x – 3x³ +2x³ – 4x = 4x² + x
5x² - x² + y² + y – 3 –y – 2y² + 5 = 4x² - y²+ 2
4u + 2u² – 2w – 3u – 9u² +w – u² = - 8u²+u-w
12ax - x +a – 10ax = 2ax - x + a
6u – 2uw +2u – 4w + 3uw = 8u + uw + 2u
-3xy + 6x – 5xy +2y – 6x = 6x - 8xy + 2y
5x + 7x – 9 = 12x - 9
9m – 3m – 4 – 4m – 9 = 2m - 4
5p – 9 + p –8 – 9p = - 3p - 17
-3a + 6 + 6a – 8 – 8a = - 5a - 2
Zadanie 2 dla x=3 i y=9
A)
-4x –7 – 3x – 8 + 6y – 10 y = - 7x - 4u - 15 = - 7 * 3 - 4 * 9 - 15 =
= - 21 - 36 - 15 = - 72
B)
4x + 4 – 7x – 0,5 - 8y + 12 y = - 3x + 4y + 3,5 = - 3 * 3 + 4 * 9 + 3,5 =
= - 9 + 36 + 3,5 = 30,5
C)
13x – 2y + 7 – 9x + y – 4 + x –3 = 5x - y = 5 * 3 - 9 = 15 - 9 = 6